The (Female) women goddness in the Kurdish myth - Shataw Bezhan Hama Rashid (QALAAI ZANIST JOURNAL, 2020)
Through a deep study of Kurdish myths from a religious and philosophical point of view, we found that they contain many beliefs and rituals, and they were interpreted as myths, such as the burial of the living and offering the sacrifices, where they were referred and searched for sources that talk about the Kurdish myth, in some of them talking about female goddess and then taking the form of a comparison between the Kurdish myth and the myths of neighboring peoples in terms of similarities and differences between them to understand the Kurdish myth. Through this research, first: Defining the myth theoretically and then the role of the gods and their types in the myth, as well as trying to define the gods, especially the female ones, the theoretical aspect includes the essence of the Kurdish myth and its characteristics, as well as the role of females in it with the search for female characteristics in myth and Kurdish folklore.